Graphitic carbon nitride (g-C3N4)-based photocatalytic materials for hydrogen evolution - Gao, Rui-Han; Ge, Qingmei; Jiang, Nan; Cong, Hang; Liu, Mao; Zhang, Yun-Qian (Frontiers in Chemistry, 2022)
The semiconductors, including TiO2, graphene, etc., produce good applications in photocatalytic water splitting for hydrogen production, which have obtained great progress in synthesis and modification. As a two-dimensional layered structure material, graphitic carbon nitride (g-C3N4), with unique properties of facile synthesis, appealing electronic band structure, and high physicochemical stability, affords good potential application in photocatalytic hydrogen evolution. However, the related low efficiency of g-C3N4 for the fast recombination rate of photogenerated charge carriers, limited visible-light absorption, and low surface area of prepared bulk g-C3N4, has called out the challenge issues to synthesize and modify novel g-C3N4-block photocatalyst. In this review, we have summarized several strategies to improve the photocatalytic performance of pristine g-C3N4 including pH, morphology control, doping with metal or non-metal elements, metal deposition, constructing a heterojunction, dye-sensitization, and so forth. As well as, the performances for photocatalytic hydrogen evolution and possible development of g-C3N4 materials are shared with the researchers interested in the relevant fields hereinto.